The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11356-021-14381-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, behavior, and erosion of uranium in vineyard soils

Abstract: Phosphate fertilization contributes to an input of uranium (U) in agricultural soils. Although its accumulation and fate in agricultural soils have been previously studied, its colloidal transport and accumulation along slopes through erosion have been studied to a lesser extent in viticulture soils. To bridge this gap, the contents and potential mobility of U were investigated in vineyard model soils in the Rhineland-Palatinate region, Germany. In addition to elevated U contents, U was expected to associate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…The applications of P fertilizers have been reported to enhance U concentrations in agricultural soils on different continents around the world. For instance, in Asia [15][16][17][18][19][20][21][22][23][24][25][26], similar in Europe [16][17][18][19][20], in Australia [21,22], in America [23][24][25][26], and in Africa [27][28][29][30][31]. This study revealed that from all reviewed articles, the concentration of U from Minjingu P fertilizers from Tanzania ranged from 200 to 600 mg kg −1 , which is similar to what is found in open-pit commercial uranium mines in Namibia.…”
Section: Introduction 1background Informationsupporting
confidence: 74%
See 3 more Smart Citations
“…The applications of P fertilizers have been reported to enhance U concentrations in agricultural soils on different continents around the world. For instance, in Asia [15][16][17][18][19][20][21][22][23][24][25][26], similar in Europe [16][17][18][19][20], in Australia [21,22], in America [23][24][25][26], and in Africa [27][28][29][30][31]. This study revealed that from all reviewed articles, the concentration of U from Minjingu P fertilizers from Tanzania ranged from 200 to 600 mg kg −1 , which is similar to what is found in open-pit commercial uranium mines in Namibia.…”
Section: Introduction 1background Informationsupporting
confidence: 74%
“…Their study was also complemented by work from Liesch et al [73], who reported that P fertilizers can be a major source of U in agricultural soils together with background concentrations. In addition to U buildup in agricultural soils, Campos et al [15] investigated the possibility of U mobility in vineyard soils in Germany's Rhineland-Palatinate region. The findings demonstrated that U in fertilized soils varied from 0.48 to 1.26 mg kg −1 , which was slightly higher than nearby non-agricultural soils (0.50 mg kg −1 ), very homogeneous along slope positions, and slightly higher in top soils.…”
Section: Europementioning
confidence: 99%
See 2 more Smart Citations
“…It is suspected though, and part of an active scientific debate, that prolonged application of phosphate rock and phosphate fertilizer can cause uranium accumulation on agricultural soils (Takeda et al 2006;Yamaguchi et al 2009;Schipper et al 2011;Bigalke et al 2017;Ratnikov et al 2020;Campos et al 2021). It is further speculated that a high concentration of uranium in agricultural soil could influence its uptake by plants through the root system in a similar way that other essential elements such as nitrogen, phosphorous, potassium, calcium, and magnesium and other supplemented micronutrients are absorbed (Velasco et al 2009;Shtangeeva 2010;Sheppard 2011;Baumann et al 2014;Harguindeguy et al 2019;Semioshkina and Voigt 2021).…”
Section: Introductionmentioning
confidence: 99%